Structural Aspects of Pt(η3–P1C2X1C2P2)(Y) Derivative Types - Milan Melník; Veronika Mikušová; Peter Mikuš (Crystals, 2023)
In this structural study, structural data are classified and analyzed for almost seventy complexes of the general formula Pt(η3–P1X1P2)(Y) (X1 = O, N, C, S, Si) and (Y = various monodentate ligands), in which the respective η3–P1X1P2 ligand forms a pair of five-membered metallocyclic rings with a common X1 atom of the P1C2X1C2P2 type. The present complexes crystallize in five crystal systems: trigonal (1×), tetragonal (1×), orthorhombic (11×), triclinic (18×), and monoclinic (39×). In 69 complexes, a η3 ligand with monodentate Y constructs a distorted square planar geometry around each Pt(II) atom. There is only one complex in which Pt(η3–P1Si1P2)(P3Ph3) constructs a trigonal–pyramidal geometry around a Pt(II) atom. The three P atoms construct a trigonal plane, and the Si atom occupies a pyramid. The structural data are discussed from various points of view, including the covalent radii of the atoms, the degree of distortion, and trans-influence. The trans-effect on the Pt-L bond distance also affects the L-PT-L bond angles, as well as the distortion of square planar geometry around Pt(II) atoms.